2013
DOI: 10.1093/humupd/dmt036
|View full text |Cite
|
Sign up to set email alerts
|

Time of insemination culture and outcomes of in vitro fertilization: a systematic review and meta-analysis

Abstract: BACKGROUND Conflicting results have been reported regarding the technique of brief insemination used in IVF. The aim of this meta-analysis was to determine if better clinical outcomes of IVF are associated with a brief co-incubation of gametes than with a standard overnight co-incubation. METHODS A computerized search was conducted of the published literature of four databases, using search terms related to gamete, time of co-incubation and outcome measure. Eligible studies compared outcomes of IVF with a brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
2
26
1
Order By: Relevance
“…4,16,17 On the other hand, Zhang et al, in a meta-analysis showed that the use of the denuding pipette during cumulus cell removal was not harmful to the clinical pregnancy or implantation rate. 15 This study found no significant difference in polyspermy, implantation, and clinical pregnancy rate in short and long co-incubation as previous studies. [9][10][11][12][13] In the short co-incubation and early cumulus cell removal, the patient had a higher premature delivery, twins and low birth weight newborn than long coincubation.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…4,16,17 On the other hand, Zhang et al, in a meta-analysis showed that the use of the denuding pipette during cumulus cell removal was not harmful to the clinical pregnancy or implantation rate. 15 This study found no significant difference in polyspermy, implantation, and clinical pregnancy rate in short and long co-incubation as previous studies. [9][10][11][12][13] In the short co-incubation and early cumulus cell removal, the patient had a higher premature delivery, twins and low birth weight newborn than long coincubation.…”
Section: Resultssupporting
confidence: 75%
“…14 Nevertheless, a meta-analysis indicates that short coincubation has a significant increase in implantation rate and clinical pregnancy rate. 15 The authors note that the conclusion may compromise due to differences in study designs and populations. In current study, sibling oocytes were randomly allocated into 2 groups to minimize the confounding factors between patients and the results showed that short co-incubation had no significant difference in fertilization, polyspermy, cleavage of embryos, blastocyst formation, implantation, clinical pregnancy, and live birth rate when compared to long coincubation which go in line with previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the advantages of a short insemination time have not been observed consistently and conflicting results have been reported (14)(15)(16). Although a meta-analysis of short insemination in IVF indicated that a reduced gamete exposure time is beneficial to clinical outcome, it also pointed out that the conclusion was compromised by design differences between studies (17).…”
Section: Discussionmentioning
confidence: 99%
“…The sperm and egg cells are incubated together at a ratio of about 75,000:1 in a culture medium. Incubating only 1-4 hours appears to result in higher pregnancy rates than incubating 16-24 hours (Zhang et al, 2013). In situations of low sperm count or motility, a sperm cell is directly injected into the egg by intra-cytoplasmic sperm injection (ICSI).…”
Section: Co-incubation Of Egg and Spermmentioning
confidence: 99%
“…With this, eggs are removed from the woman and placed in one of her fallopian tubes along with the man's sperm. This allows fertilization to take place inside the woman's body (Zhang et al, 2013).…”
Section: Co-incubation Of Egg and Spermmentioning
confidence: 99%